THE EFFECTIVENESS OF USING PARTNER READING STRATEGY IN TEACHING READING COMPREHENSION AT SMA SWADHARMA WERHDI AGUNG - Puspa Dewi; Elizabeth Z. Oroh; Paula Rombepajung (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
The purpose of this study is to find out whether the partner reading strategy is effective in teaching reading comprehension in class X SMA Swadharma Werdhiagung. Partner reading strategy is a reading activity carried out by group members consisting of two people which aims to help students understand the reading text so that it feels more effective, fun, and interesting. Researcher use pre-   experimental design with one group pre-test and post-test design and the sample of this research is class X MIA 1 student of SMA Swadharma Werdhiagung which consisted of 32 students. Instrument used in research this is a; test multiple choice test and essays test. The data calculated by the results of the student's pre-test is 44 and the post-test is 76. The value of the difference between the students' pre-test and post-test is 32. The results of this study indicated that the mean score of the post-test was higher than that of the pre-test. This means Partner Reading Strategy is very effective in increasing students' reading comprehension